Naprężenia w Narożu Ramy o Przekroju Prostokątnym - Wysiatycki, K. (Engineering Transactions, 1961)
A method is presented for the computation of the stresses in an elastic plate in the form of a corner (Fig. 1). The Airy stress function is represented by means of a polynomial, (2.2), in terms of new, curvilinear coordinates. The parameters of the stress function are found by means of the variational calculus from the condition of minimum square deviation (2.5), which leads to an equation of the fourth order, (2.15). The stresses are calculated for a corner loaded by a moment, a tension force and a. shear force.